Room Temperature Hydrogen Gas Sensing Using Zn2TiO4Thin Film - Kerketta, Ujjaval; Daniel, Thomas T.; Yadav, Vimal Kumar Singh; Paily, Roy P. (IEEE Sensors Letters, 2023)
Zn2TiO4 thin film is formed on Si/SiO2 substrate by a spin coating process and Al is used as electrodes. This device has excellent hydrogen (H2) gas sensing properties. The phase and crystal structure of the thin film was studied using X-ray diffraction. The sensor responds linearly at room temperature to H2 gas concentrations ranging from 50 to 250 ppm and shows a good sensitivity toward low ppm of H2. The response time of the sensor is about 76 s at 250-ppm H2. We could fit the sensor response to the Langmuir adsorption model.
CRIS-Team Scopus Importer:2023-03-03
Keywords: gas sensor; hydrogen; room temperature; Sensor materials; Zn